O belo na mediação pedagógica: as especificidades desta relação em ambientes virtuais de aprendizagem - Moraes, Maria Beatriz Villas Boas de (2011)
This research aimed at understanding beauty as a category of pedagogic mediation carried out by teachers using virtual learning environments as a tool for teaching. In order to accomplish objective, we sought to understand the sense of beauty in a virtual learning environment; the investigation of the potential that technology advancements offer to promote their presence; and the understanding of what features are highlighted in the subject, in the activities proposed, as well as in the interventions of the teacher that strengthen the idea of mediation involving the beauty in the course. The study was characterized as being qualitative, guided by a socio-historical approach and having, as methodological procedure, the analysis of documents comprised of the records generated in the virtual learning environment, as well as of interviews with instructors of the continuing education course, object of this investigation. The analysis of the data was carried out by general categories and subcategories that emerged from the theoretical framework underpinning the research and data. As a result, it was concluded that harmony was the sense of the beauty identified in the characteristics of the pedagogical intervention, more specifically in the role of the trainers, being also related to the consistency between the design and the teaching practice of the course, the day to day interactions, the presence of flexibility, the autonomy and authorship in the profile of the trainer and the possibilities that technological resources offered. Such evidences also allowed the development of the idea that beauty can be considered as a category of pedagogical mediation in virtual learning environments due to the fact that it favours the organization and how to understand it